KEMATANGAN INTIMASI MASA DEWASA AWAL MENURUT IMAM NAWAWI - Achmad Arroizy Subagyo; Moh. Irtadji; Mohammad Bisri (Flourishing Journal, 2021)
Abstract: Intimation is an ability to immerse his identity with the identity of others without fear of losing his own identity. This research was conducted to search for the meaning of maturity of intimation that includes sacrifice, commitment, compromise, and equal relations in the book of Riyadushshalihin the work of Imam Nawawi. The purpose of this study is to describe what and how the concept of early adulthood intimation maturity according to the perspective of Imam Nawawi. This study used a qualitative approach with Gadamerian’s hermeneutic type. Gadamerian’s hermeneutic is a method to interpret the meaning of the text by part and whole. The main data source in this study is the work of Riyadushshalihin book of Imam Nawawi. The data collected through documentation from defined text. Data analyzed using part and whole technique. Checking the validity of data is done through triangulation from the expert of sources and the book Sharh (in-depth reviews of a book). The result show that intimation maturity according to Imam Nawawi is a constant awareness of one’s self that he and the whole universe is a servant of Allah who are related to each other with behavior that is entirely based upon the laws that Allah has set over them. The intimation maturity according to him include the values of sacrifice, compromise, commitment, sincerity, and equal relations. Each divided into several aspects, there are 1) sacrifice: dedicated until the end of life, give something good to others, giving priority to others above ourselves, dedicated with earnest, give a loved one to those who need it, and bear the pain of others; 2) compromise: accepting the reason of other people, have the nature of forgiving, understanding differences of other people, to resolve issue with discussion, succumbs to the others, and idealistic; 3) commitment: the clarity of the aggreement on the commitment, have a trusteeship, made an agreemenr in commitment proportionately, have a good prejudice of other people, and the commitment is flexible; 4) equal relations: equality of responsibility for each person, the equality of rights for everyone, and legal equality for everyone; 5) sincerity: present in the presence of Almighty Allah, fear of the Almighty Allah, hoping to the Almighty Allah, and ridho against all decisions from the Almighty Allah. While the implications in psychology comparated with Erikson’s psychosocial theory. Suggestions for psychology scientists can use the result of this research as material identification intimation maturity. Researchers that interested to continue this research should use more source text and use more hermeneutic method variant. Keywords: intimation, early adulthood, Imam Nawawi